PROBLEMATIKA DAN PEMBERANTASAN KORUPSI DI INDONESIA - Muallifin, M. Darin Arif (Ahkam: Jurnal Hukum Islam, 2015)
This article discusses various issues related to the practices of corruption. Corruption is nothing new and nothing to do with the law of halal and haram. It exists long time ago and make adjustment successfully to any changes of the rule in the country. In short, corruption is part of the country’s culture. In this case, corruption includes the practices of bribery, manipulation, and any practices harmful to the country. Corruption is categorized as systemic crime which must be eradicated systematically. In the field of Law there is a theory of Legal System by Lawrence M. Friedman proposed to solve the problem of corruption including legal substance, legal structure, and legal culture. Kata kunci: Problematika Korupsi, Pemberantasan, Peran KPK, Peran Masyarakat